Becoming elderly: The Frail Elderly Day Centre as a place to deal with emotions - Fedeli, Alessia (Quaderni di Psicologia Clinica, 2023)
The article will report on a service aimed at the elderly, the Day Center for Frail Elders, a context in which, beginning with an exploration of participants’ demand, they work together to revitalize their desire. After a brief historical overview that contextualizes the birth of this type of service, the now fifteen-year experience of Elianto, Day Center for the Frail Elderly in the province of Rome, will be discussed. Both organizational and cultural aspects, resources and possible elements of development will be discussed.